PARTIKA: DESIGNING AR-BASED APPLICATIONS FOR THE SALE OF NUSANTARA FABRICS - SURYAWIJAYA, TITO; SETIAWAN, DICKY; RAHMAWATI, LIA; LAURENT, FISICHELLA; PUTRA, FEBRIANUR (Yayasan Nuraini Ibrahim Mandiri, 2024)
The post-pandemic has forced Indonesian cloth sellers in Indonesia to face changes in consumer behavior who tend to shop online. They need to find innovative ways to market products and reach potential customers. One of the problems faced is how to present traditional fabrics effectively to potential buyers. Therefore, a more creative and interactive marketing approach is needed. Using the needs analysis method to design innovative augmented reality (AR) integration in the sale of Indonesian fabrics could be an interesting solution. With AR, which will later be called PARTIKA, sellers can show potential buyers how the fabric looks in various situations, provide virtual interaction with the product, and provide detailed information. This application can thus provide a more in-depth and convincing experience, helping customers make better purchasing decisions.